Pengaruh Kepemimpinan Transformasional, Komitmen Organisasi Dan Kepuasan Kerja Terhadap Kinerja Karyawan (Studi pada Puskesmas Kalibawang, Kabupaten Kulon Progo) - Novitasari, Dwi; Fidiastuti, Fidiastuti (JURNAL RISET MANAJEMEN SEKOLAH TINGGI ILMU EKONOMI WIDYA WIWAHA PROGRAM MAGISTER MANAJEMEN, 2018)
The purpose of this study is to examine the effect of transformational leadership, organizational commitment, and job satisfaction on employee performance at Puskesmas Kalibawang, Kulon Progo. This research is a causal associative with quantitative approach. The data obtained by primary data using questionnaire method. Hypothesis testing in this reasearch are multiple linear regression analysis, F-test and T-test used to examined research model and determine the effect of independent variables to the dependent variable. The results showed a positive and significant effect of transformational leadership, organizationalcommitment, and job satisfaction on employee performance (sig. 0,000 < 0.05). T-test showed no effect of transformational leadership on employee performance (sig. 0,844 > 0,05). Organizational commitment has positive and significant effect on employee performance (sig. 0,011 < 0,05) and job satisfaction also havepositive and significant effect to employee performance (sig. 0,032 < 0,05).